Prediction of Palm Based Biodiesel Properties Through the Preparation of Empirical Equation - Joelianingsih Joelianingsih; Marcelinus Christwardana; Is Sulistyati Purwaningsih (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2019)
Biodiesel is one of plant-based fuel that has been made mandatory by the Indonesian government for using in transportation, industries, and power plants. This obligation is gradually applied as stipulated in the regulation of the Ministry of Energy and Mineral Resources 12/2015 regarding to supply, use and plant-based fuel trade as alternative fuel. The percentage of biodiesel use was increasing from 20 % in 2016 to 30 % in 2030. The quality of biodiesel has to be continuously improved to support the regulation. Biodiesel with high performance has excellent flame characteristics, high oxidation stability and easy to flow at low temperature. These characteristics are highly determined by the composition of fatty acid methyl esters (FAME). Empirical equations were formulated based on primary data to predict the essential parameters of biodiesel, consisting of oxidation stability, cloud point, Iodine value, viscosity and density. The primary data were obtained by analyzing three biodiesel samples from domestic producers and two samples of biodiesel blend between palm stearin and soybean biodiesel. Identification results showed that all three samples have different FAME profiles which consist of palm oil biodiesel, palm stearin biodiesel and palm olein biodiesel. The empirical equations were formulated using statistical software and validated by comparing the calculated results with actual biodiesel parameters. This method reduced the testing time up to 13 working days and reduced testing cost up to 67% or IDR 1 190 000 per sample. The empirical equations formulated in this study were able to predict the essential parameters of biodiesel with the error was.